The Effect Of Economic Policy On Corporate Digital Transformation, Financialization, And Green Innovation In China - Cheng, Zhuo (2024)
In recent years, China has experienced a noticeable surge in digital transformation, financialization, and green innovation. Nevertheless, these advancements remain insufficient to drive national high-quality development. Economic policy, wielded as a regulatory tool by the government to address market inefficiencies in resource allocation, holds potential as a guiding force in influencing corporate behavior towards amplifying digital transformation, financialization, and green innovation. Hence, employing the generalized method of moments (GMM) estimation and drawing upon data from 2,286 A-listed firms within the Shanghai and Shenzhen stock exchange markets across the period from 2010 to 2020, this study delves into examining the impact of economic policy on corporate digital transformation, financialization, and green innovation in China. The findings reveal a positive linkage between economic policy and corporate digital transformation, financialization and green innovation. This study suggests that the government should continue implementing favorable economic policies to encourage corporate digital transformation, financialization, and green innovation. The government should pay particular attention to non-state-owned enterprises, small-sized entities, firms in less developed districts, non-heavy-polluting industries, and non-high technology enterprises. Additionally, state-owned enterprises and larger corporations are encouraged to lead in implementing national economic policies.